2005
DOI: 10.1044/1059-0889(2005/004)
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Guide for Audiologic Tinnitus Management I

Abstract: This article explains each of these assessment components in detail. Adoption of the ATM assessment protocol by audiologists can contribute to the establishment of uniform procedures for the clinical management of tinnitus patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 48 publications
0
65
0
3
Order By: Relevance
“…Degree of annoyance of tinnitus in initial assessment and final evaluation model); TAT (counseling, considering differences and individual needs) (10,11,12) , which act on habituation, partial or total masking of tinnitus and help decrease symptom perception (14) . After amplification intervention, this study verified that all groups showed improvement in tinnitus nuisance sensation after the final evaluation (Table 1), and the analysis was made based on the difference obtained in the THI between the initial evaluation (without the use of HAs) and final evaluation (after three months of effective use of HAs), ratifying the therapeutic approaches mentioned above, which use HA associated with different forms of orientation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Degree of annoyance of tinnitus in initial assessment and final evaluation model); TAT (counseling, considering differences and individual needs) (10,11,12) , which act on habituation, partial or total masking of tinnitus and help decrease symptom perception (14) . After amplification intervention, this study verified that all groups showed improvement in tinnitus nuisance sensation after the final evaluation (Table 1), and the analysis was made based on the difference obtained in the THI between the initial evaluation (without the use of HAs) and final evaluation (after three months of effective use of HAs), ratifying the therapeutic approaches mentioned above, which use HA associated with different forms of orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Among the available treatment options, there is the use of hearing aids (HAs), the sound generator (SG) for sound therapy and habituation, cognitive therapy, counseling, diet, medication intervention and the use of a material of support -guidance booklet -about the symptom (9) . Sound therapy has been established in clinical practice and can be applied in several therapeutic approaches, such as: Tinnitus Retraining Therapy -TRT and Tinnitus Activities Treatment -TAT (10,11,12) . These approaches associate sound therapy with counseling, which consists of basic information about tinnitus, hearing loss, attention and habituation.…”
Section: Introductionmentioning
confidence: 99%
“…Henry et al, 2008b). The guidelines are based on published best practices for referring tinnitus patients (HarropGriffiths, Katon, Dobie, Sakai, & Russo, 1987;J. A. Henry et al, 2005a;J.…”
Section: Level 1 Triagementioning
confidence: 99%
“…coexisting sleep disorders and mental health disordersprimarily depression and anxiety (Dobie, 2004a;J. A. Henry, Zaugg, & Schechter, 2005a;Robinson, Viirre, & Stein, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation